Protestantism and Human Capital in Guatemala and the Republic of Korea - Rachel M. McCleary (Asian Development Bank (ADB), 2013)
Protestant missions from the United States entered the Republic of Korea and Guatemala at the same time (1884 and 1882, respectively). Yet, their impact on human capital has been divergent. The analysis presented in this paper supports the findings of Woodberry (2004, 2009, 2011) and Nunn (2009) in the case of the Republic of Korea. Mainline Protestant missions - Presbyterian and Methodist - promoted the Social Gospel and were the largest in the Republic of Korea implementing successful strategies such as using Korean (Hangul) as the lingua franca in their schools, churches, and medical facilities. Whereas the mainline Protestant denominations in the Republic of Korea successfully promoted investment in human capital, the case of Guatemala does not follow this pattern. Evangelical, Pentecostal, and neo-Pentecostal denominations and churches focused their efforts on evangelizing. Their premilliennialist beliefs translated into an eschatological urgency of conversion with little investment in human capital. As a result, institution-building requisite for investment in human capital (establishing educational institutions and medical facilities) characterized Protestant missions in the Republic of Korea, but not Guatemala. These diverging approaches to exporting Christianity have had differing longterm effects on the two societies.
hdl:11540/2085
Keywords: J24; N35; N36; O43; 330; human capital; literacy; institutions; religion; history; Humankapital; Analphabetismus; Protestantismus; Vergleich; Guatemala; Südkorea